2017
DOI: 10.1002/stc.2124
|View full text |Cite
|
Sign up to set email alerts
|

Real-time hybrid testing of a structure with a piezoelectric friction controllable mass damper by using a shake table

Abstract: Summary A structure with semi‐active control devices is usually a highly nonlinear system. To investigate the aseismic performance of such a system, real‐time hybrid testing (RTHT) can be a cost‐effective experimental method. However, a substructure with a semi‐active friction device is difficult to be tested by the RTHT, because the dynamic behavior of a friction device, which consists of sliding and sticking phases, is determined by the exerted force of the primary structure, rather than its displacement res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Sensing was performed with the actual equipment. The method is called real‐time hybrid test 32–34 . Figure 7 shows the conceptual view of the experimental system.…”
Section: Vibration Damping Control Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensing was performed with the actual equipment. The method is called real‐time hybrid test 32–34 . Figure 7 shows the conceptual view of the experimental system.…”
Section: Vibration Damping Control Experimentsmentioning
confidence: 99%
“…The method is called real-time hybrid test. [32][33][34] Figure 7 shows the conceptual view of the experimental system. The building's top floor displacement was calculated by inputting a seismic wave (i.e., JMA-Sendai-EW) recorded in the great east Japan earthquake to the computer model.…”
Section: Range Of Motion 400mmmentioning
confidence: 99%
“…Experimental results indicated that the control performance of the SAF-TMD is superior to that of the typical passive friction TMD under the same peak TMD stroke. Ju et al [26] proposed a semiactive piezoelectric friction mass damper, the desired friction force of which can be adjusted from the input voltage command of PEAs. Te performance of the damper was validated using a real-time hybrid testing method.…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in control methods, a shake table substructuring experiment is a viable option for evaluation of seismic performance of large or heavy structures that exceed the limitations of experimental apparatuses. Currently, shake table substructuring experiments are being actively investigated for earthquake engineering purposes [24][25][26][27][28][29]. To perform the substructuring experiment, two schemes can be used for achieving real-time interaction between the physical and numerical domains.…”
Section: Introductionmentioning
confidence: 99%